ELITE BIATHLETES’ SHOOTING SKILLS KINEMATICS ANALYSIS - Ivanov, D.I.; Chumakov, V.N.; Karintsev, I.A.; Lobanov, N.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze the biathlon elite’s shooting skills kinematics and give progress recommendations. Methods and structure of the study. We sampled for the study the 16-23 years old elite biathletes (n=16) qualified Masters of Sports (n=8) and Class I Athletes (n=8). Their shooting skills kinematics were tested at laboratory of the Federal Medical Research and Training Center with "Snezhinka" Winter Sports Arena of the A.A. Danilov Tchaikovsky State Academy of Physical Culture and Sports using Qualisys optoelectronic/ dynamometric digital test system plus the AMTI strain gauge platform equipped with 12 high-rate video cams. For the test purposes, we fixed markers on the front sights of the rifles, and the sample made five prone and five standing shots with no time limitations. Results and conclusion. The elite biathletes’ shooting skills kinematics tests and analysis using modern Qualisys optoelectronic/ dynamometric digital test system with the AMTI strain gauge platform made it possible to find the typical errors in the shooting skills including too high frontal pressure on the butt, rifle stoppage disorders; and deviations from the optimal aiming speeds and barrel movement amplitudes in the aiming sequence. Further studies to optimize the shooting skills kinematics are recommended for application in the elite biathletes’ training systems for technical and competitive progress.